Eksperimen Pembelajaran Kooperatif Tipe Teams Games Tournaments (Tgt) Dan Tipe Numbered Heads Together (Nht) Terhadap Hasil Belajar Matematika Ditinjau Dari Keaktifan Siswa Kelas X Semester Genap - Rosidi, Agung, Dra. Sri Sutarni, M.Pd (2016)
This research aims to determine: (1) the differences of the implementation Teams Games Tournaments and Numbered Heads Together toward mathematics learning outcomes, (2) the differences level of active students toward mathematics learning outcomes, (3) interaction between learning strategies with active students towards mathematics learning outcomes. The type of this research is experiment with quasi-experimental design. The population in this research is all students of X grade of SMA N 2 Sragen of academic year 2015/2016. Sample of this research is class X MIA 5 as an experimental class and class X MIA 4 as a control class in which 28 students in each class. The sampling technique that are use is cluster random sampling. Methods of data collection used questionnaires and tests as a principal method and documentation as an auxiliary method. Techniques of analyzed used analysis of variance two paths with different cell. Results of the data analysis with a significance level of 5% was obtained: (1) there is a significant differences between Teams Games Tournaments and Numbered Heads Together toward mathematics learning outcomes (2) there is a significant differences between the level of active students toward mathematics learning outcomes (3) there is no significant interaction between the learning strategies with active students towards mathematics learning outcomes. Keyword: Active Students, Mathematics Learning Outcomes, Numbered Heads, Together, Teams Games Tournaments.